Regulating Back Electron Transfer through Donor and π‐Spacer Alterations in Benzothieno[3, 2‐b]indole‐based Dye‐sensitized Solar Cells. Issue 21 (6th October 2020) - Nitha, P. R; Jayadev, V.; Pradhan, Sourava C.; Divya, Velayudhan V.; Suresh, Cherumuttathu H.; John, Jubi; Soman, Suraj; Ajayaghosh, Ayyappanpillai
Abstract: Three metal‐free organic D−π−A dyes with benzothieno[3, 2‐b]indole as electron donor, cyanoacrylic acid as both electron acceptor and anchoring group with benzene (BID ‐1 ), thiophene (BID ‐2 ) and furan (BID ‐3 ) as π‐spacers were designed and synthesized for application in dye‐sensitized solar cells (DSSCs). A planar and electron‐rich heterocycle such as benzothieno[3, 2‐b]indole offers better backbone rigidity and improves charge transport properties in comparison to indolo[3, 2‐b]indole donor, previously reported from our group. Additionally, we synthesized a benzothieno[3, 2‐b]indole donor grafted with longer alkyl chains which efficiently prevented the approach of oxidized species in the electrolyte coming closer to semiconductor thereby arresting recombination. A power conversion efficiency of 4.11 % was achieved for dye‐sensitized solar cells based on the furan π‐spacer benzothieno[3, 2‐b]indole dye BID ‐3 in comparison to the corresponding indolo[3, 2‐b]indole dye (IID ‐3 ) having an efficiency of 1.71 %. Detailed interfacial electrical measurements along with theoretical calculations disclosed the mechanism of back electron transfer and improvement in photovoltaic performance with respect to variation in both donor and π‐spacer. Abstract : An enhancement in efficiency was achieved with benzothieno[3, 2‐b]indole donor based dyes in comparison to indolo[3, 2‐b]indole with the same spacer and acceptor groups. This could be attributed to the increased light harvesting ability of the former along with the longer alkyl chains, reducing back electron transfer reactions.